2022
DOI: 10.1159/000527676
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status Is Associated with Prognosis in Patients with Advanced Unresectable Hepatocellular Carcinoma Treated with Atezolizumab plus Bevacizumab

Abstract: Introduction This study investigated the relationship between nutritional status, as determined by the prognostic nutritional index (PNI), and outcomes in patients with unresectable hepatocellular carcinoma (HCC) treated with atezolizumab plus bevacizumab (Atez/Bev). Methods The study analyzed 485 HCC patients treated with Atez/Bev. Results There were 342 patients with a low PNI (<47) and 143 with a high PNI (≥47). The median follow-up duration was 9.4 (6.0–14.3) months. Multivariate Cox hazards analysis sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 43 publications
0
16
1
Order By: Relevance
“…In addition to CRAFITY score, which focuses more on the malignant potential of HCC, mALBI grade and Child‐Pugh score, indicators of hepatic function, were also examined in the present study and the results confirmed the usefulness of IMABALI‐De score. Our research group has presented reports regarding the usefulness of nutritional indices as prognostic predictors of Atez/Bev, including NLR, 40 prognostic nutritional index, 41 and neo‐GPS 42 . The present study focused on hepatic function and tumor status, thus prognostic scores predicted by nutritional indicators were not included in the comparisons, though a study will soon be conducted that includes those various scores as well as the current scoring system to determine usefulness for predicting Atez/Bev prognosis after a sufficient observation period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to CRAFITY score, which focuses more on the malignant potential of HCC, mALBI grade and Child‐Pugh score, indicators of hepatic function, were also examined in the present study and the results confirmed the usefulness of IMABALI‐De score. Our research group has presented reports regarding the usefulness of nutritional indices as prognostic predictors of Atez/Bev, including NLR, 40 prognostic nutritional index, 41 and neo‐GPS 42 . The present study focused on hepatic function and tumor status, thus prognostic scores predicted by nutritional indicators were not included in the comparisons, though a study will soon be conducted that includes those various scores as well as the current scoring system to determine usefulness for predicting Atez/Bev prognosis after a sufficient observation period.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to CRAFITY score, which focuses more on the malig- prognostic nutritional index, 41 and neo-GPS. 42 The present study focused on hepatic function and tumor status, thus prognostic scores predicted by nutritional indicators were not included in the comparisons, though a study will soon be conducted that includes those various scores as well as the current scoring system to determine usefulness for predicting Atez/Bev prognosis after a sufficient observation period.…”
Section: Clinical Features Of Present Cohortmentioning
confidence: 99%
“…When analyzing progression‐free survival, we applied IPW to the Kaplan–Meier method and Cox proportional hazards models to adjust for potential imbalances between different lines of Atezo/Bev. Probabilities (propensities) associated with the first‐ and later‐line groups were calculated using logistic regression analysis with a set of covariates deemed likely to affect prognosis in patients with HCC; these included ECOG‐PS, HCC etiology, Child–Pugh score, neutrophil–lymphocyte ratio, tumor burden (maximum tumor size plus number of tumors in the liver), macrovascular invasion, and extrahepatic spread 21–31 . The IPWs were calculated using the average treatment effect method and stabilized weights method 32 …”
Section: Methodsmentioning
confidence: 99%
“…Probabilities (propensities) associated with the firstand later-line groups were calculated using logistic regression analysis with a set of covariates deemed likely to affect prognosis in patients with HCC; these included ECOG-PS, HCC etiology, Child-Pugh score, neutrophil-lymphocyte ratio, tumor burden (maximum tumor size plus number of tumors in the liver), macrovascular invasion, and extrahepatic spread. [21][22][23][24][25][26][27][28][29][30][31] The IPWs were calculated using the average treatment effect method and stabilized weights method. 32 Multivariable regression analysis with the covariates of age, sex, ECOG-PS, body mass index, HCC etiology, Child-Pugh score, α-fetoprotein, neutrophil-lymphocyte ratio, BCLC stage, and period between the date of Atezo/Bev initiation and the date Atezo/Bev therapy was approved in Japan was used to determine the prediction of the Atezo/Bev treatment lines.…”
Section: Methodsmentioning
confidence: 99%
“…Those strategies recommend that such patients be treated with durvalumab plus tremelimumab (STRIDE regimen) [4] without anti-VEGF antibodies, when an immune checkpoint inhibitor is not unsuitable. Recently, it has been reported that low EGV bleeding rate (0.8%), when an appropriate treatment for high risk EGV in unresectable HCC patients (except for those with major portal vein tumor thrombosis) before introducing Atez/Bev [5]. Screening and appropriate intervention for EGV are important for improving prognosis patients with and without HCC.…”
Section: Introductionmentioning
confidence: 99%